Strengthening Digital Literacy Education Based on Virtual Reality - Ginanjar, Asep; Zulfikasari, Sony; Nisa, Aisyah Nur Sayidatun; Hermanto, Fredy; Putri, Noviani Achmad; Wiranto, Aan Probo; Lestari, Diah Ayu Puji; Almanda, Rafi Larepa; Refiyan, Tio Putra (Universitas Negeri Semarang, 2024)
In this increasingly advanced era of technology and information, culture with local wisdom should not be forgotten. The role of local wisdom critically changes and shapes global culture to be meaningful and in accordance with the social and cultural life of society, including in the world of education. Therefore, teachers are currently required to be able to preserve local values amidst the rapid flow of technological progress. One effort that can be made through learning activities using Virtual Reality by social studies teachers in Kudus Regency. Kudus Regency is rich in local wisdom that can be used as a source of social studies learning such as the Menara Kudus Mosque, Kretek Museum, Pati Ayam Site, Kudus Traditional House, etc. Through this local wisdom-based virtual reality , it is hoped that it can train students to preserve socio-cultural conservation values through local wisdom in Kudus Regency. Therefore, to achieve this goal, special skills are needed for teachers to package local wisdom in society into digital form. These skills must be possessed by teachers as educators so that social studies learning can run more meaningfully. The training method in this activity is Community Development Practice which includes team formation, goal formulation, target community identification, needs collection and analysis, problem solution priority determination, preparation, implementation, mentoring, review and evaluation, and ending with determining new needs and targets. The ability to develop digital learning media that is relevant to the times is certainly a skill that is very much needed by teachers in this digital era. Through this community service activity, teachers can improve their skills in developing virtual reality- based learning media . Teachers can package local wisdom materials in digital form which of course will be more appropriate for the native digital generation that currently dominates school benches.